Myxoma Virus-Loaded Mesenchymal Stem Cells in Experimental Oncolytic Therapy of Murine Pulmonary Melanoma - Joanna Jazowiecka-Rakus; Aleksander Sochanik; Aleksandra Rusin; Agata Hadryś; Wojciech Fidyk; Nancy Villa; Masmudur M. Rahman; Ewa Chmielik; Lina S. Franco; Grant McFadden (Molecular Therapy: Oncolytics, 2020)
Oncolytic viruses can target neoplasms, triggering oncolytic and immune effects. Their delivery to melanoma lesions remains challenging. Bone-marrow-derived mesenchymal stem cells (MSCs) were shown to be permissive for oncolytic myxoma virus (MYXV), allowing its transfer to melanoma cells, leading to their killing. Involvement of progeny virus was demonstrated in the transfer from MSCs to co-cultured melanoma cells. The inhibitory effect of virus on melanoma foci formation in murine lungs was revealed using melanoma cells previously co-cultured with MYXV-infected MSCs. Virus accumulation and persistence in lungs of lesion-bearing mice were shown following intravenous administration of MSC-shielded MYXV construct encoding luciferase. Therapy of experimentally induced lung melanoma in mice with interleukin (IL)-15-carrying MYXV construct delivered by MSCs led to marked regression of lesions and could increase survival. Elevated natural killer (NK) cell percentages in blood indicated robust innate responses against unshielded virus only. Lung infiltration by NK cells was followed by inflow of CD8+ T lymphocytes into melanoma lesions. Elevated expression of genes involved in adaptive immune response following oncolytic treatment was confirmed using RT-qPCR. No adverse pathological effects related to MSC-mediated oncolytic therapy with MYXV were observed. MSCs allow for safe and efficient ferrying of therapeutic MYXV to pulmonary melanoma foci triggering immune effects.